Pengaruh Rasa Percaya Diri dan Motivasi Belajar terhadap Hasil Belajar Geografi Siswa Kelas X SMA Negeri 4 Singaraja - Ade Istanty Br Bangun; I Gede Astra Wesnawa; Ida Bagus Made Astawa (Jurnal Pendidikan Geografi Undiksha, 2026)
This study investigated the impact of self-confidence and learning motivation on the geography learning outcomes of tenth-grade students at SMA Negeri 4 Singaraja. Employing a quantitative approach, it drew from a population of 251 students, with a sample of 155 respondents selected using the Slovin formula at a 5% error tolerance. Data were gathered through questionnaires and documentation, then analyzed via product moment correlation, multiple linear regression, prerequisite tests, and hypothesis testing. The findings reveal a positive and significant influence of self-confidence on geography learning outcomes (t = 2.388; p = 0.000 < 0.05), alongside a similarly strong effect from learning motivation (t = 5.80; p = 0.000 < 0.05). Collectively, both variables exert a significant simultaneous impact (F = 22.368; p = 0.000 < 0.05). These results underscore the value of fostering self-confidence and motivation to boost academic performance in geography, offering practical insights for educators aiming to enhance student engagement and achievement.